AB0892 Predicting syndesmophyte formation in axial spondyloarthropathy. (12th June 2018) - Anachebe, T.; Fitzgerald, G.; Shea, F.O.
Abstract : Background: Axial spondyloarthropathy (axSpA) is a chronic inflammatory arthritis affecting the sacroiliac joints and spine. The consequence of inflammation in axSpA is new bone formation, or syndesmophytes, which can result in complete ankylosis of the spine. The pathogenesis of syndesmophyte formation is incompletely understood. It is agreed that presence of baseline syndesmophytes predicts further syndesmophytes, but other predictive factors have been difficult to define. In particular, the impact of extra-articular manifestations (EAMs) on syndesmophyte formation is unclear. Objectives: 1. To assess the burden of radiographic disease in a well-characterised axSpA cohort. 2. To investigate demographic and disease-related variables associated with syndesmophytes (specifically EAMs). Methods: A cross-sectional study of AxSpA patients was performed, comprising standardised clinical assessment and structured interviews. Validated measures of disease severity were used: BASDAI and ASDAS-CRP (disease activity), BASMI (spinal mobility), HAQ (disability), BASFI (function). Lateral x-rays of the lumbar and cervical spine were performed to quantify syndesmophytes using a validated score (mSASSS) ranging from 0–72, with higher numbers indicating a higher burden. BASRI-hip was used to determine hip involvement, assessed on x-ray of pelvis. Results: One hundred and four patients with axSpA were included: 78.8% (n=82) male, 98.1% (n=102) Caucasian, average (SD) age 50.8 (12) years and average disease duration 25 13 years. Modified New York (mNY) criteria were fulfilled by 84.6% (n=88) of the cohort. An EAM was present in 29.1% (n=30) of patients. Uveitis was the most prevalent EAM (29%), followed by inflammatory bowel disease (IBD) (18.4%) and psoriasis (17.5%). Average (SD) BASDAI was 3.9 (2.2), ASDAS-CRP 2.3 (1), BASMI 4.2 (1.9), indicating a mild to moderate disease burden in the cohort. Median (IQR) mSASSS was 9.5 (33.8), 10.6% (n=11) of patients had an mSASSS of 0% and 7.7% (n=8) had a bamboo spine. There was no significant difference in the median cervical and lumbar spine mSASSS scores (4 v 6, p>0.05). The distribution of mSASSS was similar in males and females. HLA-B27 status had no effect on mSASSS scores. Increasing mSASSS correlated significantly (p<0.05) with increasing age (rho=0.6), longer disease duration (rho=0.5), rising BASMI (rho=0.8), higher BASFI (rho=0.4) and higher HAQ (rho=0.3). Worsening hip disease, as measured by BASRI, also correlated with an increasing mSASSS (rho=0.4, p<0.01). There was also a statistically significant difference between patients who met mNY criteria compared to those that didn't (median 14.4 v 2.5, p<0.01). Patients with hypertension had a significantly higher median mSASSS score than patients without (25.4 v 7, p<0.01). Smoking status, hypercholesterolaemia, ischaemic heart disease and diabetes had no impact on mSASSS. The presence or absence of uveitis, psoriasis or IBD had no effect on syndesmophyte formation. Equally, peripheral arthritis had no effect. Patients with moderate or severe hip disease were more likely to have a higher mSASSS score (OR 3.8, 95% CI 1.5–9.3). Conclusions: In keeping with previous literature, higher mSASSS was associated with more severe disease. However, in contrast to other published studies, gender had no effect on the severity of mSASSS in our cohort. EAMs did not affect the mSASSS score, but worse hip disease did. It remains a challenge to predict which patients will develop syndesmophytes. Disclosure of Interest: None declared